2013
DOI: 10.1007/s11740-013-0462-6
|View full text |Cite
|
Sign up to set email alerts
|

Finishing of polycrystalline diamond tools by combining laser ablation with grinding

Abstract: In manufacturing polycrystalline diamond (PCD) tools, the finishing process in order to obtain the required surface and edge quality and to remove the damaged PCD layer induced by the prior manufacturing steps is mostly done by grinding. However, grinding is currently inefficient and costly due to low material removal rates and high wear of the grinding wheel. The project "Pro-PKD" aims to increase throughput and reduce tool wear by an additional laser ablation step prior to grinding. In first process investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The former technology is performed using diamond abrasives wheels; however, this introduces undesirable microcracks into the workpiece due to the diamond crystals bonded in cobalt, thus the abrasive tool can excise individual grains, leaving voids. At the same time Brecher et al (2013) reported that grinding is costly due to low material removal rates and high wear of the grinding wheel, thus it is relatively inefficient. Micro wire-EDM has emerged as a fast, economic and precise way to micro-machine electrically conductive PCD blanks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former technology is performed using diamond abrasives wheels; however, this introduces undesirable microcracks into the workpiece due to the diamond crystals bonded in cobalt, thus the abrasive tool can excise individual grains, leaving voids. At the same time Brecher et al (2013) reported that grinding is costly due to low material removal rates and high wear of the grinding wheel, thus it is relatively inefficient. Micro wire-EDM has emerged as a fast, economic and precise way to micro-machine electrically conductive PCD blanks.…”
Section: Introductionmentioning
confidence: 99%
“…Pacella et al (2015) also reported that, since cobalt is embedded in the diamond matrix, because of a difference in thermal conductivity between diamond grains and binder, important phenomena of expansion and compression between diamond and cobalt take place during the ablation process, which are also dependent on the energy density involved in laser processing. Brecher et al (2013) studied the effects of a two-step process technique (laser and grinding) in precision finishing of a 10 µm sized diamond grains PCD cutting tool. In this case a neodymium-doped yttrium orthovanadate (Nd: YVO4) laser was used after dicing and prior grinding to remove the surface layer of the cutting edge promoting improved surface finish, reduced time for manufacture and improving grinding wheel wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, both the nsand ps-laser processing has been successfully combined with precision grinding to improve the machining performance by several researchers, such as Brecher et al [15,81] employed a ns-laser combined with grinding for fabrication of PCD turning tools. In this process, the surface was micromachined using ns-laser irradiation to remove the bulk of the material, assisted by conventional grinding process to remove the residual.…”
Section: Laser Micromachining Of Diamondmentioning
confidence: 99%
“…Everson et al used nanosecond laser processing to perform the two-dimensional fabrication of microtools in polycrystalline diamond (PCD), although the phase transformation towards amorphous carbon and graphite occurred on the processed surface. In other studies [8,9] of edge shaping using PCD or chemical vapor deposition (CVD) diamond tools, the thermal impact of the nanosecond laser was used to combine laser-induced diamond graphitization with precision grinding to improve the edge quality. However, these processing methods have the problems of complex operation, low efficiency, and high cost, and the resulting edge sharpness is insufficient for application in high-precision machining.…”
Section: Introductionmentioning
confidence: 99%